2013
DOI: 10.12923/j.0044-2011/123-4/a.07
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mass media on emergence of eating disorders amongst young people

Abstract: Introduction.Anorexia is an eating disorder, which is becoming more common among young people (especially women). This problem was explored at the medical level and cultural and personal causes of denying food were analyzed.Aim. The main aim of this article is to answer the question of whether the differences in self-perception are influenced by mass media and to what extent self-perception is influenced by cultural factors.Material and methods. The research was conducted in 2011 in the form of an on-line auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Further, the authors also found that younger Facebook users recorded more body image concerns than the non-users. Therefore, it can be portrayed that media in general and social media have the possibility to adversely affect the user and the image that the user portrays in the society, the reason being that young adults strive to achieve the ideal body type as portrayed in several forms of media (Hummel & Smith, 2015; Kaźmierczak et al, 2013; Tiggemann, 2014; Walker et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Further, the authors also found that younger Facebook users recorded more body image concerns than the non-users. Therefore, it can be portrayed that media in general and social media have the possibility to adversely affect the user and the image that the user portrays in the society, the reason being that young adults strive to achieve the ideal body type as portrayed in several forms of media (Hummel & Smith, 2015; Kaźmierczak et al, 2013; Tiggemann, 2014; Walker et al, 2015).…”
Section: Resultsmentioning
confidence: 99%